ACTIVE MONITORING OF AIRBORNE ELEMENTS IN ISPARTA PROVINCE (TURKEY) - ÇOBANOĞLU, GÜLŞAH (POLISH SOCIETY MAGNESIUM RESEARCH, 2019)
Air pollutants pose a threat to biodiversity throughout the world. This study was conducted to evaluate atmospheric element accumulation in Isparta city, inducing Golcuk Nature Park, located in the Western Mediterranean Region of Turkey. It is aimed to determine the air quality and potential pollutant sources in the region through lichen biomonitoring. Specimens of the epiphytic foliose lichen Physcia aipolia (Erh. ex Humb.) Furnr. were sampled from 14 sites in the study area and analyzed by ICP - MS with reference material in order to detect 11 trace elements; Al, As, Cd, Cr, Cu, Fe, Mn, Ni, Pb, V, and Zn. The spatial distribution of these airborne elements in the study area was mapped. The results showed that the elemental sequence in terms of average concentrations measured was as follows: Ni >Cr >V >Fe >As >Al >Zn >Cu> >Cd >Mn >Pb. The results of cluster analyses of the elemental data indicated that the 3 major contaminants in the urban area were Cr, Ni, and V, probably due to the extensive use of coal in heating facilities and gasoline in vehicles. P. aipolia specimens accumulated maximal concentrations of As, Cr, Fe, Ni, and V in the northern and the south-eastern localities surrounding the city, while Cd, Pb were most abundant in the eastern edge of Golcuk Nature Park. The pollution in Isparta city with heavy metal is worse than expected, mostly due to the extensive use of coal as fossil fuel. In addition, it seems to be associated with the city's topographic and climatic characteristics, e.g. inversion effects.
Keywords: lichen; airborne elements; biomonitoring; Isparta; HEAVY-METAL POLLUTION; TRACE-ELEMENTS; AIR-QUALITY; LICHENS; ISTANBUL; TUSCANY